Potensi Chatgpt dalam Peningkatan Penjualan pada Toko Online Berbasis Syariah - M Fuad Hadziq; Nisaul Mubarokah (Pusat Riset dan Inovasi Nasional, 2025)
Sharia-based online stores faced challenges in increasing sales in the middle e-commerce competition. Technological innovations such as ChatGPT, which is one of the latest breakthroughs in the field of artificial intelligence, offer opportunities for sharia online stores to improve sales performance. The purpose of this literature study is to examine the potential of ChatGPT as a revolutionary tool for increasing sales in Sharia-based online stores. The methods used included a literature review of relevant previous research. This review includes books, journal articles, and other reliable sources, such as Google Scholar. Focusing on publications published in the last ten years, this research investigates the potential of ChatGPT to increase sales of Sharia-based online stores. The research results show that ChatGPT can help Sharia online stores improve customer communication, optimize sales conversions, provide better customer service, and increase customer loyalty. ChatGPT can provide fast, accurate, and personalized responses to customer questions, as well as provide product recommendations relevant according to customer preferences. Apart from that, ChatGPT can also help in automating repetitive tasks, thereby increasing operational efficiency. This research implied that Sharia-based online stores need to consider adopting ChatGPT as part of their marketing and customer service strategy. However, implementing ChatGPT must also pay attention to aspects of Sharia compliance and ethics in the use of technology.